Two‐Sample Mendelian Randomization Analyses Identified Lipid Species Associated With Intracranial Aneurysm Formation - Junqing Yan (Brain and Behavior)
ABSTRACT Objectives Intracranial aneurysm (IA) poses a significant health risk, and its formation involves various factors, including lipid metabolism, while former research only focused on the standard lipid. The purpose of this study is to explore 179 lipid variants' impact on unruptured intracranial aneurysms (uIA). Materials and Methods Utilizing GWAS data for lipids and uIAs, MR analyses were employed with pleiotropy, heterogeneity, and sensitivity tests. Reverse MR analyses were then conducted. Results MR analyses revealed seven lipids associated with uIAs: TAG (51:3). SE (27:1/16:1), PC (18:2_18:2), TAG (48:1), TAG (48:2), and TAG (51:3) were identified as uIA risk factors, while SE (27:1/18:1) and SM (d34:0) exhibited protective effects. Reverse MR analysis showed no bidirectional causal relationships. Conclusions This study identifies specific lipid variants causally linked to uIAs, shedding light on their roles in IA formation. These findings contribute to future research on IA risk assessment and potential therapeutic interventions.